MOTIVASI PENDIDIKAN DI SD - Idawati; Afratunnisa Suardi; Andi Triulianti; Norah Faistah (STKIP Subang, 2025)
This study discusses the concept of educational motivation in elementary schools and its role in improving the quality of learning and student engagement. The purpose of this study is to explain the meaning and objectives of educational motivation, motivation theories according to McClelland, McGregor, Maslow, and Herzberg, factors that influence student learning motivation, and managerial strategies for improving learning motivation in elementary schools. This study uses a qualitative approach with library research. Data were obtained through a review of textbooks, scientific journals, and various sources of literature relevant to educational motivation. The results of the study show that educational motivation is an important component in the learning process that serves to encourage student engagement, perseverance, and achievement. Learning motivation is influenced by internal factors such as interest, personal goals, and self-confidence, as well as external factors such as the role of teachers, parental support, and the school environment. The application of appropriate managerial strategies, such as meaningful learning, the use of interactive media, and professional support for teachers, plays an important role in optimally increasing student learning motivation. Thus, managing educational motivation is key to realizing quality learning in elementary schools.